Chemical composition determination and evaluation of the antibacterial activity of essential oils from Ruellia asperula (Mart. Ex Ness) Lindau and Ruellia paniculata L. against oral streptococci. Issue 2 (17th January 2023) - Vasconcelos, Ariana Azevedo; Veras, Idia Nara de Sousa; Vasconcelos, Mayron Alves de; Andrade, Alexandre Lopes; dos Santos, Hélcio Silva; Bandeira, Paulo Nogueira; Souza, Elnatan Bezerra de; Albuquerque, Maria Rose Jane Ribeiro; Teixeira, Edson Holanda
Abstract: This study investigated the chemical composition and evaluated the antibacterial and antibiofilm activities of essential oils (EOs) extracted from Ruellia asperula (EORA) and Ruellia paniculata (EORP) against oral streptococci. The EO constituents were analyzed by gas chromatography/mass spectrometry. The antimicrobial potential of EOs was evaluated using the minimum inhibitory concentration, minimum bactericidal concentration, and time-kill determination. Furthermore, the quantification of total biomass and the number of viable cells in the biofilms were evaluated. The major constituents of EORA were cariophylla-4(12)-8-(13)-dien-5β-ol (14.1%), (β)-caryophyllene (22.7%), and caryophyllene oxide (29.4%). For EORP, the major constituents were (β)-caryophyllene (11.0%), spathulenol (13.1%), and δ-amorphene (14.9%). The tested EOs exhibited antibacterial activity against planktonic growth and biofilm formation. Thus, the EOs from R. asperula and R. paniculata prove to be promising alternatives for bacterial growth control and biofilm formation prevention of oral streptococci. Graphical Abstract: UF0001